Fisikokimia, Mikrobiologi dan Organoleptik Sosis Daging Sapi dengan Penambahan Tepung Biji Durian (Durio zibethinus Murr) - A. Apriantini; D. Afriadi; N. Febriyani; I. I. Arief (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2021)
Durian seeds are waste products from durian fruit that have not been utilized properly. Durian seedflour contain high starch as well as tapioca flour, therefore, durian seed flour can be combined withtapioca flour as a filler for sausage dough, in order to reduce production costs of sausage products. Theaim of this study was to analyze the physicochemical, microbiological and organoleptic properties of beefsausage with the addition of 0%, 25% and 50% durian seed flour from a maximum 30% of the flour usedin making sausages. The results of physical characteristics showed that the addition of durian seed flourhad a significant effect (P <0.05) on the cohesiveness of sausages and had no significant effect (P>0.05) onother physical characteristics of sausages. The microbiological assay showed that durian seed flour didnot affect the total plate count (TPC) of beef sausages. However, the total plate count of the sausages withthe addition of 25% durian seed flour still met the SNI (Indonesian National Standard) for sausages,instead of sausages with 50% durian seed flour addition. The results of chemical analysis showed that theaddition of durian seed flour had no affect on moisture content, ash content, fat content, protein content,and carbohydrate content of the sausages. The hedonic test values on the parameters of aroma, color,texture and general appearance also showed no significant effect (P> 0.05), except for taste parameters.The hedonic quality test value also showed that the addition of durian seed flour had no different effect(P> 0.05) on the parameters of aroma, color, texture, and general appearance, but had different effect (P<0.05) on the sausage taste. The addition of durian seed flour produced a distinctive taste which coverthe flavor of sausage.